Goal Setting, Values of Binus, dan Pembelajaran Character Building di Binus University - Ruman, Yustinus Suhardi (Humaniora, 2013)
Character Building Education in this era has become concerning by so many institutions of education. Institution of education is not only preparing the student to have knowledge or become smart, cleaver, but also preparing them to become good person. Of course, there are so many definitions about good person. But in this paper, author means  that the good person is they who are not only having soft skill like communication skills, leadership skills, team work skills, initiative & enterprise skills, organization skills, problem solving and ethical decisions making skills. All these skills are very important for every people on this era. It is difficult to think about people will gain a success without mastering these skill. According to author, all the skills above, although important, they are not enough. All the skills must be built on certain values.  In this context both hard skills and soft skills should be based on certain values. As an institution of education, Binus University has certain values. They consist of trust in God, farsighted, freedom to innovate, embrace diversity and tenacious focus. The attitude and behavior of all binusian has to reveal these values. Character Building learning on this point is not only coaching the student in mastering the soft skill above, but also to internalize the values of Binus. So, Values of Binus will inspire all binusian. This paper explains the position of character building learning as a goal setting to internalize the values of binus. To describe the position of character building learning, author uses the concept social action of Talcott Parson.